Grundtvigs vurdering af Beowulf som kunstværk - Haarder, Andreas (Grundtvig-studier, 1965)
An Old Contribution to a New Debate: Grundtvig3s Evaluation of Beowulf as a Work of Art. By Andreas Haar der. Throughout the greater part of his long life Grundtvig took a serious scholarly interest in Beowulf, his most outstanding works in the field of Beowulf-scholarship being the translation of 1820 and the edition of 1861 (I). In many of his writings, including books and articles which do not deal with Beowulf in particular, he appears to be trying to answer the question how to evaluate the poem as a work of art. His attempts at solving the problem are of interest in today’s discussion of Beowulf and Literary Criticism. His praise seems in some ways to anticipate J R R Tolkien; but while he praised, his strictures were consistently upheld. In some of his unfavourable criticism he happens to share the views, not of Tolkien and many other literary critics, but of those who think a “ realistic approach” the only way towards ascertaining whether a “good” poem might not be a different thing to an Anglo-Saxon audience (II). Grundtvig’s attitude towards the concept of taste is dominated by a fusion of Neo-classic and Romantic elements in his literary criticism. It is doubtful, however, whether his criticism of Beowulf for being in some respects lacking in taste should be considered of minor interest, as betraying “ for the most part, characteristic weaknesses of neoclassic critical theory” (Malone). Some of his examples of bad taste in Beowulf do not, it is true, seem of any great relevance today; his chief argument, however, is based on considerations of structure: the use of episodes (cf. IV) and monster-fights within the framework of the poem (III). The most thorough treatment of Beowulf as a work of art appeared in Danne- Virke II (1817). It is essential to the right understanding of Grundtvig’s evaluation that he can not, through a mythical interpretation of the poem as a whole, make Beowulf a satisfactory work of art. This is evident not only because he repeats his (unfavourable) criticism as he develops his mythical interpretation, but also because he speaks of (two) kinds of value. Why does he feel compelled to distinguish between work of art (containing mythical elements) and mythical unity? There is some justification for suggesting that Tolkien’s solution was impossible for him, because he (Grundtvig) thought that the poem he had before him might be one thing, the myth, or myths, (and his own interpretation) another (V). The suggestion is corroborated if we turn to later reflections on the possible connection between the Anglo-Saxon poet (“myth-maker” ) and himself. He seems to have been reflecting on what he was doing, whether, as in 1817, his interpretation was meant to give to Beowulf a deeper (unifying) significance or he wanted to use it for his own purpose. Without wanting to lose contact with the text which he knew 21s a scholar he was to vary or supplement his mythical interpretations of the monster-fights. He remained unable, however, to change his opinion of Beowulf as a work of art once he had made up his mind about it (VI). Did not Grundtvig, the scholar, understand his own criticism of the poem by imagining an inspired “ scop” who had true claims to greatness but cared little about structure as, with many digressions, he told to his audience one story about Grendel and Grendel’s mother and another about the dragon? (VII).